Resilience Mediates the Relationship Between Loneliness and Depression in Young Adults After the Death of a Parent Due to COVID-19 - Citra Aulia; Roswiyani; Riana Sahrani (Bisma The Journal of Counseling, 2023)
The existence of the Covid-19 virus pandemic in Indonesia has resulted in high levels of loneliness and depression experienced by people, especially people who have lost their parents. The purpose of this study is to examine the relationship between loneliness and depression mediated by resilience in young adults after the death of their parents due to Covid-19. This research belongs to the type of correlational quantitative research. Participants in this study were 105 people, 75 women and 30 men, who had experienced the death of their parents due to COVID-19. Data collection in the study was carried out using the method of observation, interviews, and questionnaires, with the research instrument in the form of a questionnaire divided into four parts, the first being a questionnaire used to measure depression, loneliness and a questionnaire measuring resilience. The data obtained in the study were then analyzed using the statistical package for service solution (SPSS) application. The results of data analysis show that the resilience coefficient as a mediator is 0.082 with an LLCI value of 0.002 and a ULCI value of 0.1741. Because the BootLLCI and BootULCI ranges do not include a value of zero (0), it can be concluded that the estimation is significant and a mediating effect occurs. Based on these results, it can be concluded that resilience has the potential to reduce loneliness and subsequently reduce depression in young adults after the death of their parents due to Covid-19.